Long‐term benefits of inhaled corticosteroids in asthma: the propensity score method1. (26th June 2014) - Chanoine, Sébastien; Dumas, Orianne; Benmerad, Meriem; Pison, Christophe; Varraso, Raphaëlle; Gormand, Frédéric; Just, Jocelyne; Le Moual, Nicole; Bedouch, Pierrick; Bousquet, Jean; Kauffmann, Francine; Pin, Isabelle; et al.
Abstract: Purpose: The aim of this study was to apply a propensity score approach to assess the long‐term benefits of inhaled corticosteroids (ICS) on respiratory health in asthma. Methods: This analysis was conducted on adults with persistent asthma from the Epidemiological study on the Genetics and Environment of Asthma, a 12‐year follow‐up study. ICS exposure was assessed by questionnaire. Change in lung function over the follow‐up period, asthma control, and health‐related quality of life (asthma quality of life questionnaire) were assessed by standardized and validated methods. Results: Among 245 adults with persistent asthma, 78 (31.8%) were regularly/continuously exposed to ICS (≥6 months/year, ICS++ ) and 167 never/irregularly exposed to ICS (<6 months/year, ICS+/− ) over the follow‐up period. Compared with ICS+/− subjects, a nonsignificant trend for a slower lung function decline (mL/year) was observed in ICS++ subjects ( β [95%CI] = −11.4 [−24.9; 2.0]). The ICS++ subjects did not have better controlled asthma and higher health‐related quality of life as compared with ICS+/− subjects. Conclusions: Applying a propensity score method did not offer evidence of a statistical significant long‐term benefit of ICS on respiratory health in adults with persistent asthma regularly or continuously exposed to ICS over a long period. Copyright © 2014 John Wiley & Sons, Ltd.